MANAGEMENT OUTCOME OF SECRETORY OTITIS MEDIA - Khan, Farida; Asif, Muhammad; Farooqi, Gulshan Hussain; Shah, Shahid Ali; Sajid, Tahira; Ghani, Rehman (Journal of Ayub Medical College Abbottabad, 2006)
Background: Secretory otitis media is a common otological manifestation, that most of the time is left undiagnosed on account of unawareness and negligence in seeking early medical attention for trivial ailments. Untreated, it might end up in serious consequences in the form of poor speech and intellectual development and permanent anatomical disabilities within middle ear cleft. The objectives of the study were to determine most affected age group, the common etiological factors, to access the efficacy of medical and surgical treatment and finally to find out the complication associated with the surgical procedures. Methods: This study was conducted in the ENT, Head and Neck Surgery department of the Ayub Teaching Hospital, Abbottabad from January 2001 to December 2003.Only the diagnosed cases of SOM were included in the study. After detailed history, clinical examination, routine investigations and special investigations such as pure tone audiogram and tympanometry were carried out to confirm the diagnosis of SOM . All patients were initially treated by medical therapy. In cases of failure, underwent myringotomy with or without ventilation tube insertion and where indication present adenotonsillectomy and antral lavage was done. Follow up of cases was carried out from 18-24 months. Results: It included 87 patients, 58 were males (66.6%) and 29 females (33.3%). Majority of the patients were between 5-8 years (62%). The most common aetiological factor was rhinosinusitis (36.7%) followed by hypertrophic adenoids (34.5%). All patients were initially given medical treatment. Out of 87 patients,30 patients (34.4%) improved and 57 patients (65.5%) had no response and underwent surgery. Surgical procedures included myringotomy with and without ventilation tube insertion, adenotonsillectomy and antral lavage. Conclusion:It is concluded from this study that conservative treatment has a definite role and should be tried before any surgical step is taken however surgery is the treatment of choice in more resistant cases. Key Words: Secretory otitis media, otitis media with effusion, myringotomy